Pengaruh Kunjungan Wisatawan, Tingkat Hunian Hotel, Pengeluaran Wisatawan Terhadap Penyerapan Tenaga Kerja dan Pertumbuhan Ekonomi di Provinsi Bali - Windayani, Ida Ayu Ratih Sasmitha; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 2, Februari 2016 (pp. 115 - 285), 2017)
The  purpose  of   this  study  was  to  analyze  1)  Effect  of  tourist  arrivals,  hotel  occupancy  rates  and  tourist  expenditure on  employment,  2) Effect of tourist arrivals, hotel occupancy rates, tourist expenditure and employment to economic growth, 3) The indirect effect tourist arrivals, hotel occupancy rates and tourist expenditure on employment through  economic  growth. This research was conducted in the province of Bali. The objects on the study include tourist arrivals, hotel occupancy rates, tourist expenditure, employment and economic growth. Data collection methods used in this study include non-participant observation and in-depth interviews.  Data  analysis  technique  used  is  the analysis track / path  analysis  and Sobel test to analyze the indirect influence through an intervening variable. Based on the results obtained and the conclusions that the visit Travellers tourist expenditure has no direct effect on employment in the province of Bali, while the occupancy rate of the hotel direct and significant impact on employment.
Keywords: Kunjungan Wisatawan; Tingkat Hunian Hotel; Pengeluaran Wisatawan; Penyerapan Tenaga Kerja; Pertumbuhan Ekonomi